LONGITUDINAL MICROBIOME ANALYSIS REVEALS EARLY BACTEROIDES PREDOMINANCE AS A POTENTIAL BIOMARKER FOR AUTISM SPECTRUM DISORDER: A PEDIATRIC CASE STUDY WITH COBALAMIN METABOLIC IMPLICATIONS (Experimental biology, 2025)
The intricate relationship between gut microbiota and neurodevelopmental disorders has emerged as a critical area of research, particularly in autism spectrum disorder (ASD). This case study presents groundbreaking longitudinal evidence of gut microbiota alterations preceding ASD diagnosis in a two-year-old female infant. The research aimed to characterize early-life microbiome dynamics and their potential connection to subsequent ASD development, contributing to our understanding of the gut-brain axis in neurodevelopmental disorders. Using shotgun metagenomic sequencing, we tracked the infant's microbiome composition from birth through 18 months of life, comparing it with 215 control samples. Our methodology incorporated comprehensive bioinformatic analysis using the bioBakery suite, including MetaPhlAn 4 for taxonomic profiling and HUMAnN 3 for functional profiling. The study revealed a persistent and significant elevation in Bacteroides abundance, particularly B. fragilis, from the first month of life, preceding clinical ASD manifestation. Notably, functional analysis demonstrated an increased presence of cobalamin biosynthesis genes associated
Keywords: Autism Spectrum Disorder; Bacteroides fragilis; cobalamin; gut metagenome